A systematic review and meta-analysis of real-world data predictors for conversion to progressive multiple sclerosis - Solís-Tarazona, Luis Rafael; Molina-Castaño, Maria; Barea-Moya, Lucas; Galan, Joana; Raket, Lars Lau ; 0000-0001-7099-2314; Gil-Perotin, Sara (Multiple Sclerosis and Related Disorders, 2025)
Background: Available fluid biomarkers, neuroimaging techniques, and clinical assessments may enhance prediction of conversion to secondary progressive multiple sclerosis (SPMS). Objectives: : To identify robust real-world predictors of MS progression in the literature. Methods: : A systematic review was conducted in EMBASE. A total of 20,338 MS patients from 64 eligible studies were included. A p-value meta-analysis and a tipping point analysis were performed to assess associations with MS progression and EDSS. Results: Among CSF biomarkers, GFAP (p = 6.2 × 10⁻¹⁰) and CHI3L1 (p = 1.7 × 10⁻¹¹) demonstrated consistent aggregated associations with disease progression. In serum, NfL (p = 2.5 × 10⁻13) and GFAP (p = 1.4 × 10-8) showed strong association with concurrent EDSS and disease progression. Spinal cord lesions (p = 9.4 × 10⁻¹¹) and iron rim lesions (p = 4 × 10⁻⁶) were the strongest radiological predictors. Among clinical assessment tools, significant associations were found with concurrent EDSS, but prediction of progression was limited. Conclusion: Fluid biomarkers, particularly CSF GFAP, CHI3L1, and serum NfL, along with spinal cord lesions and iron rim lesions on MRI, provide consistent evidence for predicting MS progression. There is a need for harmonized and accessible outcome measures in real-world datasets.
Keywords: Accessibility; Biomarkers; Cerebrospinal fluid; Expanded Disability Status Scale; Multiple Sclerosis; Neuroimaging; Progression